Cremation under fire: a review of bioarchaeological approaches from 1995 to 2015 - Gonçalves, David (2017)
The study of bioarchaeological evidence associated with burials is essential for achieving a global perspective on cremation as a funerary practice, its chronological and geographical distribution, as well as its inner sociocultural and technological diversity. However, for that purpose, similar and consistent analyses must be adopted by bioarchaeologists to enable intra- and inter-sites comparisons. The 1995–2015 literature encompassing 84 geographically representative articles concerning bioarchaeological studies of burned human skeletal remains is reviewed herein. The objective was to assess methodological variability. Information concerning colour, fragmentation, skeleton completeness, ‘skeletal region’ representation, non-human funerary assemblage, pre-burning condition of the remains, minimum number of individuals, biological profile, trauma and pathologies was considered. The results demonstrate that certain methods were used by almost all researchers. That was the case for colour description (91 %), skeleton completeness (91 %), minimum number of individuals (96 %), age-at-death (100 %) and sex of the individuals (95 %). Researchers are much more divided about the implementation of the remaining methods. Methodological choices also vary. The asymmetries in the selection of the analyses that are undertaken can lead to different interpretations and conclusions of the contexts under study. This may prevent consistent comparisons within the same site and between different sites. We emphasize the need for bioarchaeologists to discuss and standardize analytical procedures for studying cremated remains.